ANALISIS KEBUTUHAN PENGEMBANGAN SUBJECT SPECIFIC PEDAGOGY ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Rino Richardo; Adhetia Martyanti; Suhartini Suhartini (Journal of Mathematics and Mathematics Education, 2018)
Abstract: Indonesian law number 14 of 2005 concerning Teachers and Lecturers suggests that pedagogical competence is an ability to manage students’ learning process, with one of the indicators is teachers must have an ability to plan a teaching and learning process. The planning includes all units of learning devices called as Subject Specific Pedagogy (SSP). Understanding SSP is a crucial matter to be developed since teachers do not have understanding about it comprehensively and students are less facilitated with critical thinking skills. The objective of the study is describing the needs of teachers and students for the development of Subject Specific Pedagogy (SSP) based on ethnomatematics to improve critical thinking skill. The method used in the study is qualitative with survey approach. This research is conducted at State Junior High School (SMPN) 1 Piyungan Yogyakarta. The research subjects are mathematics teachers and students at the eighth grade by using purposive sampling technique. Data collection techniques are carried out questionnaires through interviews. Data analysis uses descriptive qualitative analysis. Questionnaire data and interviews are analyzed through data reduction, data presentation, and conclusion. The result show that: (1) Teachers do not have comprehensive knowledge related to Subject Specific Pedagogy (SSP) and they still have obstacles in developing it, (2) Teachers do not understand the ethnomatematics concept in mathematics learning, (3) Teachers have never developed worksheets and tasks which facilitate students in critical thinking, and (4) Students are still difficult in solving mathematics problems, especially problems that require critical thinking skill.Keywords: Ethnomatematics, SSP, Critical, Needs, Development.